Перша в Україні знахідка гриба Staurosphaeria lycii Rabenh. з Українського степового природного заповідника (відділення «Крейдова флора» - Гарбуз, Д.; Акулов, Олександр Юрійович; Harbuz D.; Akulov О. (Львівський національний університет імені Івана Франка, 2021)
The reserve was established in 1988 to protect natural complexes formed on chalk rocks on the right bank of the Siversky Donets River. There are few groups of fungi were investigated from this territory. Information about Staurosphaeria lycii (Didymosphaeriaceae, Pleosporales, Dothideomycetes, Ascomycota), which is the first find in Ukraine territory, is given.
The first find of fungus Staurosphaeria lycii Rabench. from Ukrainian Steppe Natural Reserve ("Kreidova flora" branch)
Keywords: Lycium barbatum; Staurosphaeria; Coelomycetes; arid territories; cretaceuos